A comprehensive review of peptic ulcer disease: epidemiology, experimental models, and mechanistic insights - Singh, Laliteswar Pratap; Chatterjee, Sandip; Kar, Sanjeeb Kumar (Creative Pharma Assent, 2025)
Background: Peptic ulcer disease (PUD) is one of the most common gastrointestinal disorders, resulting from an imbalance between aggressive and protective factors, leading to mucosal erosion. Various factors influence its pathogenesis, including Helicobacter pylori infection, NSAID use, and oxidative stress. Objective: We review PUD epidemiology, varying experimental models, and mechanistic insights into PUD and promising therapeutics. Methodology: We systematically reviewed previous literature on PUD, including epidemiological trends, commonly used in vivo, and molecular mechanisms. Results and discussion: The global prevalence of peptic ulcer disease (PUD) follows an epidemiological pattern influenced by geography, lifestyle, and genetic factors. Experimental models using ethanol, NSAIDs, or Helicobacter pylori induction provide valuable insights into disease progression and pathophysiology. Emerging trends: Recent research in peptic ulcer disease focuses on molecular mechanisms, gut microbiome interactions, personalized therapies, and novel pharmacological agents. Molecular studies explore genetic and epigenetic factors influencing ulcer formation, while microbiome research examines the role of gut bacteria beyond H. pylori. Personalized treatment approaches use genetic profiling and biomarkers to enhance efficacy and reduce toxicity. Additionally, emerging pharmacological agents aim to improve acid suppression, promote mucosal healing, and develop more effective H. pylori eradication strategies. Conclusion: A deeper understanding of PUD pathophysiology through epidemiological studies and experimental models can aid in developing novel, targeted therapies. Future research should focus on alternative treatments, including phytochemicals and probiotics, to enhance ulcer prevention and management.